Emotions in Knowledge Production - Candiotto, Laura (My University, 2023)
This synoptic review surveys the philosophical literature on the epistemology of emotions to identify the role of emotions in knowledge production. It analyses their evaluative, motivational, hermeneutical and social functions as embedded in epistemic practices and cultures. The focus on situated epistemic emotions stresses the importance of developing an ethics of knowledge production. The review introduces some new proposals for fostering inquiry in this field, drawing from agency-based accounts of emotions (enactivism, in particular) and virtue epistemology.
Emoce při tvorbě znalostí
Keywords: theories of emotion; epistemic emotions; science-making; epistemic cultures; virtue epistemology; situated affectivity; agency-based accounts of emotions; enactivism; teorie emocí; epistemické emoce; tvorba vědy; epistemické kultury; epistemologie ctnosti; situované affectivity; agency-based popisu emocí; enactivism